Endoluminal rescue of false lumen graft deployment in TEVAR for type B aortic dissection: a case report and literature review - Zhu, Hong Jiang; Yan, Feng; Zhao, Peng Peng (Frontiers in Cardiovascular Medicine, 2024)
Background Thoracic endovascular aortic repair (TEVAR) has increasingly become the preferred surgical intervention for Stanford type B aortic dissection (TBAD). The primary objective of this procedure is to seal the primary entry tear to promote positive aortic remodeling. However, the increased use of TEVAR has also led to a rise in surgical complications. Among these, the accidental deployment of the stent into the false lumen is a rare but serious complication that can result in aortic false lumen rupture and inadequate perfusion of abdominal organs. Case summary This case report described a 78-year-old man who presented to our hospital with sudden onset chest and back pain and was subsequently diagnosed with TBAD via aortic CTA. As conventional medical therapy failed to alleviate his chest pain, the patient underwent TEVAR. During the procedure, a complication arose when the distal end of the endograft was mistakenly deployed into the false lumen, leading to insufficient perfusion of the abdominal organs. Recognizing this issue intraoperatively, an additional endograft was promptly inserted at the distal end to reroute blood flow back to the true lumen of the aorta, thereby restoring visceral perfusion. Post-intervention, the patient's chest pain improved, and he was successfully discharged from the hospital. Conclusion Accidental deployment of a endograft into the false lumen during TEVAR is a rare but serious complication. Intraoperative angiography plays a crucial role in rapidly and accurately identifying this issue by detecting insufficient perfusion of abdominal organs. The use of intravascular ultrasound may help reduce the incidence of this complication. Endovascular repair is an effective emergency strategy to quickly redirect blood flow back to the true lumen, making it the preferred method for managing such emergencies.